Outcome of Surgery of Vestibular Schwannomas in a Tertiary Care Hospital in Bangladesh - Uddin, Kazi Hafiz; Islam, Md Joynul; Ashadullah, ATM; Elahy, Fazle; Ahmad, Misbah Uddin; Sonia, Suraiya Jahan; Alam, Shafiul; Rashid, Mirza Md Hafizur (Bangladesh Journal of Neurosurgery, 2021)
Background: Presenting symptoms, treatment considerations, and outcome are strongly related to the extension of vestibular schwannomas (VS). The aim of the current retrospective study was to analyze the clinical features, microsurgical treatment, and outcome of VS with brainstem compression. Methods: Seventy patients presented with VS who had undergone operative procedures performed in our unit from 2017 to 2019. The facial nerve function and hearing assessment was done according to House-Brackmann [HB] grading and pure tone audiometry (PTA) respectively. All patients were operated by retro-mastoid suboccipital approach. Results: Most patients had large tumors and had no useful hearing (85%), had disabling cerebellar ataxia (92.86%) and presented with features of raised intracranial pressure (48.57%). Large sized tumors were in 32.86% and giant sized tumors were in 57.14% cases. Complete tumor excision was carried out 92.86% and anatomical preservation of facial nerve was achieved in 73.85% cases. Hearing preservation was achieved in 4 patients. Cerebrospinal fluid leak with or without meningitis and transient lower cranial nerve paresis were common complications. The mortality rate was 7.14%. Conclusions: Complete tumor excision with good facial nerve preservation can be achieved in large vestibular schwannomas. Hearing preservation is difficult in larger tumors. Primary microsurgical resection is an appropriate management option for large VS. In our experience, this goal can be achieved safely and successfully by using the retrosigmoid approach. Bang. J Neurosurgery 2021; 10(2): 175-181